Relationship Between Age Of Menarche With Primary Dismenorea In Adolescents - Rusydi, Riska; Tamtomo, Didik Gunawan; Kartikasari, Lilik Retna (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: The first period is also known as menarche. The age of early menarche is one of the factors causing menstrual disorders. one of the menstrual disorders is dysmenorrhoea. Dysmenorrhea or also known as menstrual pain that is felt before or during menstruation in the lower abdomen. In Indonesia, 54.89% were found experienced primary dysmenorrhea. Objective: to determine the relationship between the age of menarche and the incidence of primary dysmenorrhoea in adolescents. Materials and Methods: This research is an observational analytic study with a cross sectional approach. Sampling was carried out by multistage random sampling on 133 female adolescents at Senior High School Number 9 and Senior High School Number 15 in Padang. Data of dysmenorrhoea and age of menarche was obtained by filling out a questionnaire that had been provided, it was analysis by chi square statistical test at the significant level α = 0.05. Results: 93.8% of respondents who have early menarche age experience primary dysmenorrhea. Relationship between the age of menarche and the incidence of primary dysmenorrhea in adolescents (p= 0.004, OR=4.933). Conclusion: Adolescents with early menarche have a 4.933 times greater risk of experiencing primary dysmenorrhea. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 123-126